2019
DOI: 10.1007/s00606-019-01570-w
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous caudicle reconfiguration in Dactylorhiza fuchsii: A new self-pollination mechanism for Orchideae

Abstract: Deceptive plants represent a strategy that promotes outcrossing and protects against facilitated selfing. However, deception does not eliminate the possibility of autonomous self-pollination when pollinators are scarce or absent. Spontaneous autogamy is widespread in Orchidaceae, but the scale, mechanism, time of appearance and effectiveness remain underestimated. Using field and laboratory observations and experiments, for the first time, we documented the possibility of autonomous self-pollination in the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In the Orchidaceae and subfamily Asclepiadaceae, for example, deposition of a single pollinium containing millions of pollen grains is more than sufficient to fertilize all ovules of a flower (Johnson and Edwards, 2000). However, even in these plant groups some species have mechanisms enabling selfing to occur should cross-pollination fail (Yamashiro and Maki, 2005;Tałałaj et al, 2019). Species such as S. umbratica, which produce one or a few ovules per flower, are unlikely to experience pollen-limitation following a single visit by a pollinator.…”
Section: Discussionmentioning
confidence: 99%
“…In the Orchidaceae and subfamily Asclepiadaceae, for example, deposition of a single pollinium containing millions of pollen grains is more than sufficient to fertilize all ovules of a flower (Johnson and Edwards, 2000). However, even in these plant groups some species have mechanisms enabling selfing to occur should cross-pollination fail (Yamashiro and Maki, 2005;Tałałaj et al, 2019). Species such as S. umbratica, which produce one or a few ovules per flower, are unlikely to experience pollen-limitation following a single visit by a pollinator.…”
Section: Discussionmentioning
confidence: 99%
“…Pollination occurs in different taxonomic groups of insects (Hymenoptera, Diptera, and/or Coleoptera, Ostrowiecka et al., 2019; Wróblewska et al., 2019), which can promote cross‐pollination and/or geitonogamy (Hedrén & Nordström, 2009; Ostrowiecka et al., 2019). Moreover, the mechanism of spontaneous caudicle reconfiguration in three Dactylorhiza taxa exists, but results in less than 1% autogamous pollination in the studied populations (Tałałaj et al., 2019; Wróblewska et al., 2024). Dactylorhiza majalis blooms first, from the beginning of May to the beginning of June.…”
Section: Methodsmentioning
confidence: 99%
“…Little research has been done on the pollination strategy of Gennaria diphylla. It is said to be predominantly autogamous (Claessens & Kleynen, 2011;Tałałaj & Skierczynski, 2015;Marrero et al, 2019;Tałałaj et al, 2019). Fernandes et al (2003) reported Noctuidae, Syrphidae and Tipulidae as (potential) pollinators.…”
Section: Introductionmentioning
confidence: 99%